##### Ads

related to: LHS

Here's the first as an example of the layout:

**LHS**= cosθcotθ = cosθ * cosθ/sinθ ... because cotθ = 1/tanθ = cos^2θ / sinθ = (1 - sin...1 Answers · Science & Mathematics · 28/01/2015

http://s1169.photobucket.com/user/chibuckt/media/IMG_20140808_0001_zps3addacb7.jpg.html?filters[user]=127216769&filters[recent]=1&sort=1&o=0

3 Answers · Science & Mathematics · 11/08/2014

Have both axles inspected for excessive wear and also the hub bearings by the wheels. Secondly, have the tires rebalanced. Don't care how old they are. Third, replace the left front strut assembly. The...

3 Answers · Cars & Transportation · 23/10/2007

sin x + sin 2x = sin x + 2 sin x cos x = sin x (1 + 2 cos x) 1 + cos x + cos 2x = 1 + cos x + (2cos^2 x - 1) = cos x + 2 cos^2 x = cos x (1 + 2 cos x) ∴ (sin x + sin 2x)/(1 + cos x + cos 2x) = sin x(1 + 2 cos x)/[cos x(1 + 2 cos x)] = sin x/cos x = tan x. Note that the double-angle identities for sine and cosine were...

3 Answers · Science & Mathematics · 25/05/2012

Expand the RHS -2[sin(x/2)cos(y/2)+sin(y/2)cos(x/2)][sin(x/2)cos(y/2)-sin(y/2)cos(x/2)]=-2[sin^2(x/2cos^2(y/2)-sin^2(y/2)cos^2(x/2)] using difference of two squares change the cos^2(y/2)=1-sin^2(y/2) and cos^2(x/2)=(1-sin^2x/2) to obtain -2(sin^2(x/2)-sin^2(y/2)) convert the sin^2(x/2) and sin^2(y/2) to the double...

1 Answers · Science & Mathematics · 20/06/2013

9)

**LHS**= cos ( x + y - y )**LHS**= cos...**LHS**= sin x - ( sin y / cos y )*cos x**LHS**= (sin x cos y - sin y cos x ) / cos...2 x cos^2 y - sin^2 x sin^2 y )**LHS**= ( sin^2 x - sin^2 x sin^2 y - sin...2 Answers · Science & Mathematics · 18/04/2013

Doubtful, if this is possible. I would present it on the mathematics category for a firm answer.

1 Answers · Science & Mathematics · 13/11/2012

**LHS**= ( sin x + sin 3x) / ( cos x + cos 3x )**LHS**= 2 sin ( 2x) cos (x) / 2 cos (2x ) cos ( x )**LHS**= tan 2x**LHS**= RHS QED1 Answers · Science & Mathematics · 03/05/2013

Since cos^2(x)=(1+cos2x)/2 so we obtain cos2x=2cos^(x)-1 also we know sin2x=2sin(x)cos(x) now if we put these things in what u have writen we will have [(2sin(x)cos(x)]/sin(x) - (2cos^(x)-1)/cos(x) = 2cos(x)-2cos(x)+ (1/cos(x))=sec(x)

2 Answers · Science & Mathematics · 10/11/2012

**LHS**= 1 + tan^2 x**LHS**= (cos^2 x + sin^2 x) / cos^2 x**LHS**= 1 / cos^2 x**LHS**= RHS QED3 Answers · Science & Mathematics · 25/11/2009

##### Ads

related to: LHS